Gadolinium pyrochlore type nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid

The preparation of Gd2Ti2O7 gadolinium-coated chlorite structure supported Ni-based catalyst was solved by sol-gel method, which poor structural thermal stability, easy oxidation and carbon deposit during the hydrogen production process of acetic acid autothermal reforming, and achieved high activity, stability and anti-carbon deposit performance of the catalyst.

CN119771425APending Publication Date: 2025-04-08CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038997.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing nickel-based catalysts have problems such as poor structural thermal stability, easy oxidation and carbon accumulation during the hydrogen production process of acetic acid, resulting in the deactivation of the catalyst.

Method used

The Gd2Ti2O7 gadolinium cocochloride structure was prepared by sol-gel method to form a Ni-Gd-Ti-O active center, which improved the stability of the catalyst and the resistance to carbon deposit.

Benefits of technology

In the acetic acid autothermal reforming reaction, the catalyst showed good activity, stability, sintering resistance and carbon deposit resistance. The conversion rate of acetic acid was close to 100%, the yield of hydrogen was stable, and the catalyst activity remained stable for 10 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771425A_ABST
    Figure CN119771425A_ABST
Patent Text Reader

Abstract

The invention relates to a Gd2Ti2O7 gadolinium pyrochlore type nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid. The invention provides a novel catalyst with high activity, carbon deposition resistance and high stability aiming at the problem of inactivation of the existing catalyst in the autothermal reforming process of acetic acid. The molar composition of the catalyst is (NiO) a (GdO1.5) b (TiO2) c, a ranges from 0.75 to 0.86, b ranges from 1.29 to 1.32, and c ranges from 1.29 to 1.32. According to the invention, Gd and Ti are introduced by using a sol-gel method to synthesize the nickel-based catalyst which takes Gd2Ti2O7 gadolinium pyrochlore as a carrier and has a Ni-Gd-Ti-O active center. According to the catalyst, the stability of the catalyst and the yield of hydrogen are effectively improved, and the generation of byproducts such as methane and acetone is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a gadolinium pyrochlore type nickel-based catalyst for producing hydrogen through autothermal reforming of acetic acid, belonging to the field of producing hydrogen through autothermal reforming of acetic acid. Background Art

[0002] Hydrogen is a clean energy with advantages such as high energy density and wide availability. Biomass is regarded as a carbon-neutral resource. Biomass can be converted into biomass oil by rapid pyrolysis, and biomass oil can be divided into oil phase and water phase. Among them, the water phase contains a high content of acetic acid (33wt.%), and the production of hydrogen through the reforming process has broad development prospects.

[0003] The acetic acid autothermal reforming (ATR) hydrogen production combines the advantages of steam reforming reaction (SR) and partial oxidation reaction (POX), in which the POX reaction can act as a heat source, and the energy released by it provides the necessary energy for the SR reaction, that is, by adjusting the amount of acetic acid, water and oxygen to control the generation and release of heat during the ATR reaction, the whole process remains thermoneutral. Therefore, the acetic acid autothermal reforming reaction can be started quickly without the need to provide additional external heat.

[0004] Transition metal catalysts, especially nickel-based catalysts, have been widely used in catalytic reforming to produce hydrogen due to their high activity in cracking CH and CC bonds. The acetic acid molecule CH3COOH is adsorbed and activated on the Ni-based catalyst, and is transformed through steps such as dehydrogenation and dehydroxylation, i.e., CH3COOH*→CH3COO*→CH3CO*→CH2CO*→CH2*+CO*→CH*, where intermediates such as CH2* and CH* are further deeply dehydrogenated to form C* species, and a large amount of C* aggregates and deposits on the catalyst surface to form carbon deposits, covering the active sites on the catalyst, which reduces the reaction activity of the catalyst. In addition, nickel-based catalysts are prone to sintering under high temperature conditions, resulting in catalyst deactivation.

[0005] In order to solve the challenges faced by Ni-based catalysts, it is very important to select appropriate carriers or additives to promote the efficient conversion of acetic acid. The present invention prepares a Gd2Ti2O7 gadolinium pyrochlore structure-supported Ni-based catalyst by a sol-gel method to form a Ni-Gd-Ti-O active center for use in the hydrogen production process of acetic acid autothermal reforming.

[0006] The Gd2Ti2O7 gadolinium pyrochlore structure (r A / r B = 1.75) belongs to the cubic Fd̅3m space group, where Gd 3 +Located at position 16(c), it bonds to eight O²⁻ atoms to form distorted GdO8 hexagonal bipyramids that share edges with six equivalent GdO8 hexagonal bipyramids and six equivalent TiO6 octahedra. There are two shorter (2.21Å) and six longer (2.51Å) Gd-O bond lengths. 4+ Located at the 16(d) position, it bonds with six equivalent O²⁻ atoms to form a TiO6 octahedron, which shares corners with six equivalent TiO6 octahedra and edges with six equivalent GdO8 hexagonal bipyramids. The tilt angle of the corner-sharing octahedron is 48°, and all Ti-O bond lengths are 1.97Å. This edge-sharing structure gives the crystal good high-temperature phase stability, provides a stable reaction interface for acetic acid conversion, enhances the dispersion of the active component Ni, and improves the stability of the catalyst. There are two inequivalent O²⁻ sites in this structure. In the first O²⁻ site, O²⁻ bonds with four equivalent Gd³⁺ atoms to form a corner-sharing OGd4 tetrahedron. In the second O²⁻ site, O²⁻ bonds with two equivalent Gd³⁺ and two equivalent Ti in a 4-coordinate geometry. 4 ⁺ Atomic bonding; two unequally coordinated O 2- It will produce electronic transitions and has strong activity. It can generate oxygen vacancies through the jumping mechanism, effectively promoting the mobility of lattice oxygen, which is beneficial to the efficient combination of O* species in the reaction gas with CH3* and C* formed during the dehydrogenation of CH* to generate CO and CO2, thereby eliminating carbon deposits and improving the catalyst's anti-carbon deposition performance.

[0007] The innovation of the catalyst composition and structure of the present invention enables the catalyst to exhibit good activity, stability, resistance to sintering and resistance to carbon deposition in the autothermal reforming reaction of acetic acid, and improves the conversion rate of acetic acid and the selectivity of hydrogen, showing excellent catalytic properties. Summary of the invention

[0008] The present invention prepares a nickel-based catalyst with Gd2Ti2O7 gadolinium pyrochlore as a carrier by a sol-gel method, which solves the problems of poor thermal stability of the catalyst structure and catalyst deactivation caused by oxidation and carbon deposition in the process of hydrogen production by acetic acid autothermal reforming of existing catalysts. The preferred catalyst of the present invention is applied to the reaction process of hydrogen production by acetic acid autothermal reforming. Under the reaction temperature of 700°C, the conversion rate of acetic acid is close to 100%, and the yield of hydrogen is stabilized at about 2.78 mol-H2 / mol-HAc.

[0009] Technical solution of the present invention:

[0010] The invention aims at the characteristics of acetic acid autothermal reforming, and prepares a nickel-based catalyst supported by Gd2Ti2O7 gadolinium pyrochlore by a sol-gel method. The molar composition of the catalyst of the invention is (NiO)a (GdO 1.5 ) b (TiO2) c , wherein a is 0.75-0.86, b is 1.29-1.32, and c is 1.29-1.32; the weight percentage composition calculated as oxides is: nickel oxide content is 14.0%-16.0%, gadolinium oxide content is 58.3%-59.7%, titanium dioxide content is 25.7%-26.3%, and the sum of the weight percentages of each component is 100%.

[0011] The specific preparation and reaction steps are as follows:

[0012] 1) Weigh a certain amount of nickel nitrate and gadolinium nitrate, add anhydrous ethanol, and stir at room temperature until all are dissolved to obtain solution 1;

[0013] 2) Weigh citric acid in a 1:1 ratio of the total molar number of metal cations and dissolve it in anhydrous ethanol to obtain solution 2;

[0014] 3) Weigh a certain amount of butyl titanate solution, slowly drop it into the 2# solution, and keep stirring; then weigh ethylene glycol in a 1:1 ratio of the total molar number of metal cations, slowly drop it into the 2# solution to obtain a mixed solution, and finally drop the mixed solution into the 1# solution, and stir it in a 70°C water bath until it becomes a gel, take it out and place it in a 105°C oven to dry for 12 hours to obtain a catalyst precursor;

[0015] 4) The obtained catalyst precursor was heated to 800°C in a tube furnace at a heating rate of 10°C / min and kept calcined for 4 hours. After being reduced in a H2 flow at 700°C for 1 hour, a Gd2Ti2O7 structure and a nickel metal phase were obtained to form a gadolinium pyrochlore-type nickel-based catalyst, whose typical structure is shown in the X-ray diffraction diagram (see Appendix). Figure 1 ), the mesoporous structure distribution is shown in the attached Figure 2 shown.

[0016] Beneficial effects of the present invention:

[0017] 1) The present invention adopts a sol-gel method to construct a Gd2Ti2O7 gadolinium pyrochlore type nickel-based catalyst. After hydrogen reduction, Ni is highly dispersed on the Gd2Ti2O7 carrier to form a Ni / Gd2Ti2O7 structure containing a Ni-Gd-Ti-O active center, which is beneficial to the adsorption and conversion of CH3COOH, H2O, and O2 into products such as H2 and CO2.

[0018] 2) In the Gd2Ti2O7 structure constructed by the present invention, Gd 3+ Bonded to eight O²⁻ atoms, forming a distorted GdO8 hexagonal bipyramid, while Ti 4⁺ forms TiO6 octahedrons with O²⁻. These octahedrons share edges with GdO8 hexagonal bipyramids, which plays a key role in the stability of the crystal structure, provides a stable reaction interface for acetic acid conversion, and improves the stability of the catalyst.

[0019] 3) In the Gd2Ti2O7 gadolinium pyrochlore structure constructed by the present invention, the 16c and 16d cation sites in the unit cell are filled with Gd and Ti atoms, and the remaining anion sites 48f and 8a are occupied by oxygen atoms, and the migration of oxygen is supported by the existence of ordered oxygen vacancies at the 8b position. The Gd2Ti2O7 structure has a Ʃ3(111)(110) twin interface, and the formation of the twin boundary occurs along the (111) crystal plane direction, and there is a 71° gap between the two symmetrically arranged crystals. ° ±0.1 ° The angular rotation of the twin boundary causes a 3~5% distortion in the atomic structure, which increases the bond lengths of Gd-Gd and Ti-Ti, that is, compared with 0.63nm in the ordered structure, they increase to 0.66±0.03nm and 0.65±0.02nm on the (110) plane, respectively. Oxygen migrates between the two 48f and 48f anion positions in the (100) direction through a vacancy hopping mechanism. The average migration energy barrier of oxygen at the twin boundary is 1.23eV, which can effectively promote the migration of oxygen ions in the lattice, thereby generating oxygen vacancies, allowing oxygen in the lattice to migrate to the surface of pyrochlore, which is beneficial for C* species and CO* to combine with O* radicals to form CO and CO2, thereby increasing the gasification rate of CHx* and C*, thereby effectively inhibiting the aggregation of carbon deposit precursors on the catalyst surface to form carbon deposits, and improving the anti-carbon deposition performance of the catalyst.

[0020] 4) The present invention introduces rare earth metal Gd as the A-site metal cation, and Gd with a larger ionic radius 3+ It can cause lattice distortion and deformation stress of the framework, which is conducive to the formation of defect sites. At the same time, the strong lanthanide shrinkage effect of Gd atoms can change the local electron density of surrounding atoms and promote the formation of Ti 4+ / Ti 3+ The transition of the two valence states is beneficial to improving the adsorption capacity of the catalyst surface for CH3COOH, H2O, and O2, thereby enhancing the catalytic performance. In addition, the interaction between Ni and the carrier reduces the mobility of Ni through the electron transfer between Gd-O-Ti-Ni, inhibiting the aggregation and growth of Ni grains. In catalysts with larger specific surface areas, Ni 0 It shows a larger dispersion and can more effectively inhibit the active component Ni 0 of sintering.

[0021] 5) The catalyst of the present invention was used in the autothermal reforming of acetic acid to produce hydrogen. The results showed that the catalyst of the present invention has the advantages of resistance to carbon deposition, oxidation resistance, sintering resistance, stable catalytic activity and high hydrogen yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : X-ray diffraction spectrum of the catalyst of the present invention.

[0023] Figure 2 : BJH pore size distribution diagram of the catalyst of the present invention. DETAILED DESCRIPTION

[0024] Reference example one

[0025] Weigh 2.349g of Ni(NO3)2·6H2O, add 100mL of anhydrous ethanol, stir at room temperature until completely dissolved to obtain solution 1#; weigh 10.635g of citric acid, dissolve in 30 mL of anhydrous ethanol to obtain solution 2#; weigh 14.473g of butyl titanate, slowly drop it into solution 2#, keep stirring; weigh 3.141g of ethylene glycol, slowly drop it into solution 2# to obtain a mixed solution, and finally slowly drop the mixed solution into solution 1#, stir it until it is colloid under 70°C water bath conditions, take it out and place it in an oven at 105°C to dry for 12h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 800°C in a tubular furnace at a heating rate of 10°C / min, and kept roasting for 4h to form TiO2 and NiO phases, that is, CDUT-NT catalyst was obtained. The molar composition of the catalyst is (NiO) 0.80 (TiO2) 4.25 The weight percentage composition of the oxides is: 15.0% nickel oxide and 85.0% titanium dioxide.

[0026] The activity evaluation of acetic acid autothermal reforming reaction was carried out in a continuous flow fixed bed reactor. The catalyst was ground and tableted, then sieved into 20-40 mesh particles, 0.2 g was weighed and loaded into the reactor, and reduced in H2 at 700°C for 1 hour; then the mixed solution of acetic acid and water was injected into the vaporizer by a constant flow pump for vaporization, mixed with oxygen, and nitrogen was used as the internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2 / N2=1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and the raw gas was introduced into the reaction bed. The reaction conditions were 700°C, normal pressure, and space velocity of 10000-35000 mL / (g-catalyst·h), and the reaction tail gas was analyzed online by gas chromatograph.

[0027] The catalyst CDUT-NT was investigated for its activity in acetic acid autothermal reforming. Under the reaction conditions of atmospheric pressure, space velocity of 25000mL / (g-catalyst·h), reaction temperature of 700°C, and raw gas molar composition of acetic acid / water / oxygen / nitrogen of 1.0 / 4.0 / 0.28 / 3.9, the hydrogen yield of the CDUT-NC catalyst was low, about 2.34mol-H2 / mol-HAc, the selectivity of CO2 was about 55.3%, the selectivity of CO was about 41.2%, and the selectivity of CH4 was about 3.5%, indicating that the catalyst activity was low and there were more by-products. The CDUT-NC catalyst was characterized by low-temperature nitrogen adsorption, and the results were: the specific surface area was 14.6m 2 / g, pore volume is 0.043cm 3 / g, and the average pore diameter is 11.9nm.

[0028] Embodiment 1

[0029] Weigh 2.346g of Ni(NO3)2·6H2O and 5.873g of Gd(NO3)3·6H2O, add 100mL of anhydrous ethanol, and stir at room temperature until completely dissolved to obtain 1# solution; weigh 7.164g of citric acid, dissolve in 30mL of anhydrous ethanol to obtain 2# solution; weigh 4.428g of butyl titanate, slowly add it dropwise to 2# solution, and keep stirring; then weigh 2.115g of ethylene glycol, slowly add it dropwise to 2# solution to obtain a mixed solution, and finally slowly add the mixed solution dropwise to 1# solution, and stir in a 70°C water bath until it becomes a gel, take out and place in an oven at 105°C to dry for 12 hours to obtain a catalyst precursor. The obtained catalyst precursor was heated to 800°C in a tube furnace at a heating rate of 10°C / min and kept calcined for 4 hours. After being reduced in a H2 flow at a temperature of 700°C for 1 hour, a nickel-based catalyst with a Ni / Gd2Ti2O7 structure with a Gd2Ti2O7 gadolinium pyrochlore structure as the main body, a nickel metal phase, and a Ni-Gd-Ti-O active center, namely, CDUT-NGT catalyst, was obtained. Its typical crystal structure is shown in the attached Figure 1 As shown; the catalyst molar composition is (NiO) 0.08 (GdO 1.5 ) 1.30 (TiO2) 1.30 The weight percentage composition of the oxides is: 15.0% nickel oxide, 59.0% gadolinium oxide, and 26.0% titanium dioxide.

[0030] The catalyst CDUT-NGT was investigated for its activity in acetic acid autothermal reforming. Under the reaction conditions of atmospheric pressure, space velocity of 25000mL / (g-catalyst·h), reaction temperature of 700℃, and raw gas molar composition of acetic acid / water / oxygen / nitrogen of 1.0 / 4.0 / 0.28 / 3.9, the performance of the catalyst was stable, the acetic acid conversion rate was 100%, the hydrogen yield was maintained at 2.78mol-H2 / mol-HAc, the CO2 selectivity was about 57.6%, the CO selectivity was about 42.3%, the CH4 selectivity was 0.10%, no by-product acetone was produced, and as the reaction proceeded, the activity of the catalyst could remain stable for 10 hours; the CDUT-NGT catalyst was characterized by low-temperature nitrogen adsorption, and the results were as follows: the specific surface area was 31.3m 2 / g, pore volume is 0.114 cm 3 / g, the average pore size is 23.5nm, forming a mesoporous structure. Its typical mesoporous structure features are as follows Figure 2 The characterization results show that the active structure of the catalyst has no obvious phase change and no sintering, and can effectively inhibit the production of by-products such as methane and acetone, and has the characteristics of high catalytic activity and stable hydrogen yield.

Claims

1. Application of Gd2Ti2O7 gadolinium pyrochlore type nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: 0.1-0.3 g of the catalyst is reduced in H2 at a temperature of 700° C. for 1 h, purged with nitrogen, and a mixed gas with a molar ratio of acetic acid / water / oxygen / nitrogen of 1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5) is introduced through the catalyst bed to react at a reaction temperature of 600-800° C. The catalyst is prepared by the following method: a certain amount of nickel nitrate and gadolinium nitrate are weighed, anhydrous ethanol is added, and stirred at room temperature until all are dissolved to obtain a 1# solution; citric acid is weighed in a 1:1 ratio with the total molar number of metal cations, and dissolved in anhydrous ethanol to obtain a 2# solution; a certain amount of butyl titanate solution is weighed, and it is slowly added dropwise to the 2# solution. The mixture was stirred in a tube furnace, and the temperature was raised to 800°C at a heating rate of 10°C / min and the calcination was maintained for 4 hours. After H2 reduction treatment, a Ni / Gd2Ti2O7 structure with Ni-Gd-Ti-O as the active center was formed, and the Ni-based catalyst supported by Gd2Ti2O7 gadolinium pyrochlore was obtained. The molar composition of the oxide is (NiO) a (GdO 1.5 ) b (TiO2) c , wherein a is 0.75-0.86, b is 1.29-1.32, and c is 1.29-1.32; the weight percentage composition calculated as oxides is: nickel oxide content is 14.0%-16.0%, gadolinium oxide content is 58.3%-59.7%, titanium dioxide content is 25.7%-26.3%, and the sum of the weight percentages of each component is 100%.

2. The use of the Gd2Ti2O7 gadolinium pyrochlore type nickel-based catalyst according to claim 1 in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: The catalyst has a weight percentage composition of 15.0% nickel oxide, 59.0% gadolinium oxide and 26.0% titanium dioxide, calculated as oxides.